3D Printing of Poly-ε-Caprolactone (PCL) Auxetic Implants with Advanced Performance for Large Volume Soft Tissue Engineering - Park, Jeong Hun; Park, Hyun Ji; Tucker, Sarah Jo; Rutledge, Sarah K.; Wang, Lizhen; Davis, Michael E.; Hollister, Scott J. (Advanced Functional Materials, 2023)
A successful 3D printing of a novel 3D architected auxetic for large-volume soft tissue engineering is reported. The 3D auxetic design is analyzed through finite element (FE) simulation and created by selective laser sintering (SLS) of Poly-ε-caprolactone (PCL) for further in-depth mechanical and biological analysis. High initial flexibility and nonlinear stress–strain response to the uniaxial compression are achieved despite the use of PCL, which is one of the biomaterials that is clinically approved but has the disadvantage of having relatively stiff and linear mechanical properties. The high mass transport properties of the 3D auxetic are also demonstrated by not only high cell viability but also cell functionality within a cell-laden hydrogel in large sizes of the auxetic. The outstanding mechanical and biological performance of the 3D auxetic is a consequence of the synergistic effect of the novel architected auxetic design combined with the inherent printing characteristic of SLS. The current study demonstrates great potential of SLS-based printing of 3D auxetics toward the development of clinically viable 3D implants for the reconstruction of large-volume soft tissues.
Keywords: 3-D printing; 3D-printing; Auxetics; Finite element analyse; Finite elements simulation; Large volumes; Mechanical analysis; Performance; Poly(ε caprolactone); Soft tissue engineering; 3D printing; auxetics; finite element analysis; selective laser sintering; soft tissue engineering